Bypass during Liver Transplantation: Anachronism or Revival? Liver Transplantation Using a Combined Venovenous/Portal Venous Bypass—Experiences with 163 Liver Transplants in a Newly Established Liver Transplantation Program. (2nd March 2015) - Mossdorf, Anne; Ulmer, Florian; Junge, Karsten; Heidenhain, Christoph; Hein, Marc; Temizel, Ilknur; Neumann, Ulf Peter; Schöning, Wenzel; Schmeding, Maximilian
Abstract : Introduction . The venovenous/portal venous (VVP) bypass technique has generally become obsolete in liver transplantation (LT) today. We evaluated our experience with 163 consecutive LTs that used a VVP bypass. Patients and Methods . The liver transplant program was started in our center in 2010. LTs were performed using an extracorporal bypass device. Results . Mean operative time was 269 minutes and warm ischemic time 43 minutes. The median number of transfusion of packed cells and plasma was 7 and 14. There was no intraoperative death, and the 30-day mortality was 3%. Severe bypass-induced complications did not occur. Discussion . The introduction of a new LT program requires maximum safety measures for all of the parties involved. Both surgical and anaesthesiological management (reperfusion) can be controlled very reliably using a VVP bypass device. Particularly when using marginal grafts, this approach helps to minimise both surgical and anaesthesiological complications in terms of less volume overload, less use of vasopressive drugs, less myocardial injury, and better peripheral blood circulation. Conclusion . Based on our experiences while establishing a new liver transplantation program, we advocate the reappraisal of the extracorporeal VVP bypass.